Social support and self-compassion: Their influence on work-family conflict among mothers employed as nurses - Putri, Desthia Tasya Mahardhika; Hijrianti, Udi Rosida; Syafitri, Diany Ufieta (Jurnal Ilmiah Psikologi Terapan, 2024)
Nurses bear the responsibility of providing care to patients amidst demanding work schedules. For a mother working as a nurse, balancing roles in both profession and family becomes a priority; failure to achieve this balance may lead to conflict. This study investigates the predictive ability of social support and self-compassion on work-family conflict among nurse mothers. The study involved 143 nurse mothers recruited through accidental sampling methods. Instruments employed included the Multidimensional Scale of Perceived Social Support (MSPSS), self-compassion scale, and work-family conflict scale. Multiple linear regression analysis revealed that social support and self-compassion collectively predict work-family conflict among nurse mothers (R²= 0.130, F = 10.487, p= 0.00). The ability of social support and self-compassion to predict work-family conflict was 13%, with the remaining variance attributable to unexamined variables in this study. The implications of this study suggest that managing work-family conflict necessitates social support from family, supervisors, colleagues, and friends. Furthermore, enhancing self-compassion through self-kindness, acknowledging common humanity, and fostering mindfulness while reducing self-judgment, isolation, and over-identification could prove advantageous.